2013
DOI: 10.1371/journal.pone.0071221
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Immunity Triggered by a Single, Latent Virus in Mus musculus: Combined Costimulation- and Adhesion- Blockade Decrease Rejection

Abstract: The mechanisms underlying latent-virus-mediated heterologous immunity, and subsequent transplant rejection, especially in the setting of T cell costimulation blockade, remain undetermined. To address this, we have utilized MHV68 to develop a rodent model of latent virus-induced heterologous alloimmunity. MHV68 infection was correlated with multimodal immune deviation, which included increased secretion of CXCL9 and CXCL10, and with the expansion of a CD8dim T cell population. CD8dim T cells exhibited decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Adams et al elegantly showed that memory T cells from mice that had multiple infections could cross-react with alloantigens and mediate the rejection of skin allografts in the setting of co-stimulation blockade 43 . Specific pathogens such as Listeria monocytogenes 44 , γ-herpes virus 45 and cytomegalovirus (CMV) 46,47 have been mechanistically defined in heterologous alloimmune processes. Indeed, in mice, these infections drive T-cell differentiation and the loss of CD28 expression, leading to indifference to CD28–B7 co-stimulation blockade 35 .…”
Section: Memory T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adams et al elegantly showed that memory T cells from mice that had multiple infections could cross-react with alloantigens and mediate the rejection of skin allografts in the setting of co-stimulation blockade 43 . Specific pathogens such as Listeria monocytogenes 44 , γ-herpes virus 45 and cytomegalovirus (CMV) 46,47 have been mechanistically defined in heterologous alloimmune processes. Indeed, in mice, these infections drive T-cell differentiation and the loss of CD28 expression, leading to indifference to CD28–B7 co-stimulation blockade 35 .…”
Section: Memory T Cellsmentioning
confidence: 99%
“…Targeting VLA-4 in conjunction with co-stimulation blockade also increased survival in rodent transplant models compared to co-stimulation blockade alone 113 . Thus, inhibition of LFA-1 or VLA-4 in combination with co-stimulation blockade might have a synergistic effect, particularly in the setting of heterologous memory, whereby inhibition of integrin binding might selectively target cells that are resistant to co-stimulation blockade 47,100 .…”
Section: Targeting Alloreactive Memory Cellsmentioning
confidence: 99%
“…It has been previously reported that as CD8+ T cells become activated, they downregulate their CD8 surface expression, resulting in a population of so-called CD8 dim cells [26]. In our analyses, we noted that during sepsis a population of CD8 dim CD44 hi cells could be identified.…”
Section: Resultsmentioning
confidence: 49%
“…Furthermore, we identified a population of CD8 dim CD44 hi cells that emerged during sepsis which was significantly decreased in alcohol fed animals compared with water-fed animals 72 hours after CLP. Several published reports [26, 46] suggest that these may be antigen-specific CD8+ T cells that have downregulated the CD8 co-receptor following TCR ligation, and if so these findings would indicate a delay in expansion of antigen-specific CD8+ T cells following sepsis in the setting of chronic alcohol exposure. Future experiments using tools to track antigen-specific cell responses are likely warranted to further elucidate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was attributed to cross-reactive CD4 memory responses to Leishmania (15). Latent infections of B6 mice with murine gamma herpesvirus 68, a murine Epstein-Barr virus (EBV) homolog, accelerate BALB/c skin allograft rejection mediated by long-lasting viral antigen-specific CD8 memory responses (16,17). In transplant recipients receiving calcineurin inhibitorbased immunosuppression, persistent alloimmune responses generated by chronic viral infections do not become "exhausted" and may contribute to graft injury (18)(19)(20)(21).…”
Section: Specific Organisms Contribute To Allograft Rejection Via Innmentioning
confidence: 99%